Family Based Premarital Teenager Education in Islamic Education Perspective in Kaili Community in Palu - Andi Markarma (State Institute of Islamic Studies (IAIN) Palu, 2017)
The widespread of premarital pregnancy is caused by rampant promiscuity among female teenagers. The promiscuity occurs due to lack parents’ supervision. Female teenagers often break religious, ethical, moral and customary norms. Therefore, it is important to provide teenagers with pre-marriage education materials. Islam teaches its adherents not to be in hurry in everything except in five things: burial of corpse, paying debts, serving travelers, repenting, and marrying. This study attempts to examine family-based premarital sex education in Islamic education perspectives in the Kaili community in the Palu Valley. The researcher used a quantitative-descriptive approach to see the relationship of research variables. The results show that, the majority of housewife knowledge about premarital education is very low. This certainly affect the lack of premarital sex education of their young daughters. Low knowledge of housewives and young female regarding premarital sex education because families do not teach and socialize moral, ethical, and ethical values effectively in their communities.